PENYULUHAN DAN PELATIHAN KOMUNIKASI TENTANG PENDIDIKAN SEKS UNTUK ANAK USIA DINI - Enis Fitriani; Yahmun Yahmun; Endang Sumarti (JPM PAMBUDI, 2021)
The rise of cases of violence against minors causes concern for parents. Sexual violence against children is not only perpetrated by people we do not know, but can occur from those closest to us. Therefore, it is very important for parents to teach sex education to their children from a young age. The objectives of this program were to provide information, understand, and provide experiences about sex education for children at PAUD Al-Ihsan Malang Regency with the parents as the target. This program ran through socialization and training where parents got information about communicating simple sex education for early childhood with materials: seven aspects of children's education in Islam and modern education, the concept of "where do I come from?", and apply simple sex education in daily life. This program had been successfully proven by the parents’ enthusiasm in asking questions, sharing experiences, discussing, and practicing communication